Islamic Justice and Maqashid Syariah: A Study of the Balance between Justice and Benefit - Dasrianto, Vito; Elva Mahmudi; Arminsyah; Said, Dede Hafirman (Kartika: Jurnal Studi Keislaman, 2025)
This paper explains that Islamic courts have a central role in upholding the law based on the principles of justice and benefit in accordance with sharia teachings. This study aims to examine the application of Maqasid Syariah the main objectives of sharia, which include the protection of religion, life, intellect, descendants, and property in the judicial process, in order to achieve a balance between al-‘adl (justice) and al-maslahah (benefit). The research method used is a literature study with a normative-juridical approach, involving an analysis of classical and contemporary Islamic legal sources, as well as a review of relevant judicial decisions. The results of the study indicate that the integration of Maqasid Syariah in judicial practice can maintain the relevance of law to social dynamics, while ensuring that the principle of justice remains the primary foundation. Achieving this balance requires an active role of judges in interpreting sharia arguments comprehensively and contextually, so that legal decisions are not only normatively valid but also beneficial for the welfare of the community